(3cJGH GdeYWjGJs - (3GbdjOSs
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg fSHI C Edi L cfSHI H Edi O hEPG HOdfG cGfJ fSHI C Edi H cfSHI L Edi O s
(3BNQgG (B:s
(3eQHY g` O eSGhjkG deQHY g` L ajLYd eQHY C g` eTJQckG ajchf GdSWM hPdc eG CQOfG HjGfg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1460s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdQjGVjGJs